FRI0267 CLINICAL CORRELATES AND RELEVANCE OF UCLA GIT 2.0 FOR ESOPHAGITIS AND INDICATION FOR ESOPHAGOGASTRODUODENOSCOPY IN REAL-LIFE PATIENTS WITH SYSTEMIC SCLEROSIS. (2nd June 2020) - Zampatti, N.; Garaiman, A.; Jordan, S.; Becker, M. O.; Maurer, B.; Dobrota, R.; Distler, O.; Mihai, C.
Abstract : Background: The gastrointestinal (GI) tract is frequently involved in systemic sclerosis (SSc). The University of California Los Angeles Scleroderma Clinical Trial Consortium Gastrointestinal Tract Instrument 2.0 (UCLA GIT 2.0) is validated to capture GI morbidity in patients with SSc (1). The routine clinical investigation of GI involvement in these patients is not standardized and there is no consensus about when and how frequently an esophagogastroduodenoscopy (EGD) should be performed. Objectives: The main aim of this study was to analyze the capacity of UCLA GIT 2.0 to identify patients with erosive esophagitis in an unselected, real-life SSc patients' cohort. Secondary aim was to determine whether the UCLA GIT 2.0 could discriminate SSc patients for whom an expert rheumatologist would recommend an EGD. Methods: We selected patients fulfilling the ACR/EULAR 2013 criteria for SSc from the Zurich cohort, having completed at least once the UCLA GIT 2.0 questionnaire. We reviewed the medical charts of SSc patients from 2013 to 2019 and recorded data on EGD. We analyzed by univariable logistic regression several parameters, including UCLA GIT 2.0, considered as potentially associated with 1) the referral to EGD and 2) macroscopic esophagitis according to the Los Angeles criteria. Results: We identified 346 patients (82.7% female, median age 63 years, median disease duration 10 years, 23% with diffuse cutaneous SSc) satisfying the inclusion criteria, who filled in 940 UCLA GIT 2.0 questionnaires. From 940 visits, 31 were excluded because EGD was done within 3 months before completing the UCLA GIT 2.0. In the 909 remaining visits, EGD was recommended by the expert rheumatologists in 128 cases. In logistic regression, UCLA GIT 2.0 total score and some of its subscales, but also the modified Rodnan skin score (mRSS) and esophageal and stomach symptoms by past medical history, associated with the referral to EGD (Table 1 ). We found data on 177 EGD performed in 150 patients, meaning that 49 EGD were performed on indication by another physician. In logistic regression, mRSS and esophageal symptoms correlated with esophagitis, while neither the total ULCA GIT 2.0 score nor the reflux subscale or any of the other subscales showed an association with esophagitis (Table 2 ). Conclusion: In a real-life setting, UCLA GIT 2.0 subscales (reflux, distention/bloating, social functioning, emotional wellbeing) and total score strongly associated with expert interpretation of gastroesophageal symptoms and consecutive referral to EGD. However, they showed no correlation with esophagitis on EGD. The main clinical association of esophagitis was the presence of esophageal symptoms. References: [1]Khanna D, et al. Reliability and validity of the University of California, Los Angeles Scleroderma Clinical Trial Consortium Gastrointestinal Tract Instrument. Arthritis Rheum. 2009;61(9):1257-63. Disclosure of Interests: Norina Zampatti: None declared, Alexandru Garaiman: None declared, Suzana Jordan: None declared, Mike O. Becker: None declared, Britta Maurer Grant/research support from: AbbVie, Protagen, Novartis, congress support from Pfizer, Roche, Actelion, and MSD, Speakers bureau: Novartis, Rucsandra Dobrota: None declared, Oliver Distler Grant/research support from: Grants/Research support from Actelion, Bayer, Boehringer Ingelheim, Competitive Drug Development International Ltd. and Mitsubishi Tanabe; he also holds the issued Patent on mir-29 for the treatment of systemic sclerosis (US8247389, EP2331143)., Consultant of: Consultancy fees from Actelion, Acceleron Pharma, AnaMar, Bayer, Baecon Discovery, Blade Therapeutics, Boehringer, CSL Behring, Catenion, ChemomAb, Curzion Pharmaceuticals, Ergonex, Galapagos NV, GSK, Glenmark Pharmaceuticals, Inventiva, Italfarmaco, iQvia, medac, Medscape, Mitsubishi Tanabe Pharma, MSD, Roche, Sanofi and UCB, Speakers bureau: Speaker fees from Actelion, Bayer, Boehringer Ingelheim, Medscape, Pfizer and Roche, Carina Mihai: None declared